Identification and expression analysis of the lipid phosphate phosphatases gene family reveal their involvement in abiotic stress response in kiwifruit - Yang, Yaming; Chen, Lijuan; Su, Gen; Liu, Fangfang; Zeng, Qiang; Li, Rui; Cha, Guili; Liu, Cuihua; Xing, Libo; Ren, Xiaolin; Ding, Yuduan (Frontiers in Plant Science, 2022)
Lipid phosphate phosphatases (LPPs) are a key enzyme in the production and degradation of phosphatidic acid (PA), which plays an important role in plant growth, development, stress resistance and plant hormone response. Thus far, little is known about the LPP family genes in kiwifruit (Actinidia spp.). According to this study, 7 members in the AcLPP family were identified from the whole genome of kiwifruit, the subcellular localization predictions were mainly on the plasma membrane. Chromosomal localization analysis showed that the AcLPP genes were unevenly distributed on 5 chromosomes, it was determined to have undergone strong purifying selection pressure. There were 5 duplicate gene pairs and all underwent segmental duplication events. The LPP genes of kiwifruit were conserved when compared with other plants, especially in terms of evolutionary relationships, conserved motifs, protein sequences, and gene structures. Cis-regulatory elements mainly included hormone response elements and abiotic response elements. Functional annotation of GO revealed that AcLPP genes were closely related to phosphatase/hydrolase activity, phosphorus metabolism and dephosphorylation. AcLPP genes family were predicted to be targets of miRNA. Transcript level analysis revealed that the AcLPP family played diverse functions in different tissues and during growth, development, and postharvest storage stages. qPCR analysis showed that the members of AcLPP gene family might be regulated by ETH, ABA, GA3, and IAA hormone signals. The family members were regulated by the stress of salt stress, osmotic stress, cold stress, and heat stress. These results would provide a basis and reference for studying the agricultural characteristics of kiwifruit and improving its stress resistance.